Lactobacillus rhamnosus GG Attenuates Lipopolysaccharide-Induced Inflammation and Barrier Dysfunction by Regulating MAPK/NF-κB Signaling and Modulating Metabolome in the Piglet Intestine. Issue 5 (6th February 2020) - Mao, Jiangdi; Qi, Siri; Cui, Yanjun; Dou, Xiaoxiao; Luo, Xin M; Liu, Jianxin; Zhu, Tao; Ma, Yanfei; Wang, Haifeng
ABSTRACT: Background: Probiotic Lactobacillius rhamnosus GG (LGG) shows beneficial immunomodulation on cultured cell lines in vitro and in mouse models. Objective: The aim was to investigate the effects of LGG on intestinal injury and the underlying mechanisms by elucidating inflammatory signaling pathways and metabolomic response to LPS stimulation in the piglet intestine. Methods: Piglets (Duroc × Landrace × Large White, including males and female; 8.6 ± 1.1 kg) aged 28 d were assigned to 3 groups ( n  = 6/group): oral inoculation with PBS for 2 wk before intraperitoneal injection of physiological saline [control (CON)] or LPS (25 μg/kg body weight; LPS) or oral inoculation with LGG for 2 wk before intraperitoneal injection of LPS (LGG+LPS). Piglets were killed 4 h after LPS injection. Systemic inflammation, intestinal integrity, inflammation signals, and metabolomic characteristics in the intestine were determined. Results: Compared with CON, LPS stimulation significantly decreased ileal zonula occludens 1 (ZO-1; 44%), claudin-3 (44%), and occludin (41%) expression; increased serum diamineoxidase (73%), D-xylose (19%), TNF-α (43%), and IL-6 (55%) concentrations; induced p38 mitogen-activated protein kinase (p38 MAPK; 85%), extracellular signal-regulated kinase (ERK; 96%), and NF-κB p65 phosphorylation (37%) ( P < 0.05). Compared with LPS stimulation alone, LGG pretreatment significantly enhanced the intestinal barrier by upregulating expressions of tight junction proteins (ZO-1, 73%; claudin-3, 55%; occludin, 67%), thereby decreasing serum diamineoxidase (26%) and D-xylose (28%) concentrations, and also reduced serum TNF-α expression (16%) and ileal p38 MAPK (79%), ERK (43%) and NF-κB p65 (37%) phosphorylation levels ( P < 0.05). Metabolomic analysis showed clear separation between each group. The concentrations of caprylic acid [fold-change (FC) = 2.39], 1-mono-olein (FC = 2.68), erythritol (FC = 4.62), and ethanolamine (FC = 4.47) significantly increased in the intestine of LGG + LPS piglets compared with the LPS group ( P < 0.05). Conclusions: These data suggest that LGG alleviates gut inflammation, improves intestinal barrier function, and modulates the metabolite profile of piglets challenged with LPS. This trial was registered at the Zhejiang University (http://www.lac.zju.edu.cn) as ZJU20170529.